Development of Combined Methods Using Non-Destructive Test Methods to Determine the In-Place Strength of High-Strength Concretes - Demir, Tuba; Ulucan, Muhammed; Alyamac, Kursat Esat (Mdpi, 2023)
This study aims to develop combined methods with dual and triple use of different non-destructive test (NDT) methods and to examine the effectiveness of these methods. For this purpose, nine different high-strength concrete series were produced, and destructive and NDT methods were applied to these samples on the 3rd and 90th days. Surface hardness, ultrasonic pulse velocity, and penetration resistance were considered from NDT methods. Analyses were made on the response surface method using the NDT measurements and compressive strength values obtained, and four different mathematical models were developed. Models 1, 2, and 3 were designed with dual use of NDT methods, and model 4 was designed with triple use. The absolute relative deviation values for all the developed models' early and final-age strengths were below 10%. It is of great importance to determine concrete quality with high accuracy and practicality, especially in places like Elazig, where there are thousands of newly constructed buildings since the Sivrice-Elazig earthquake, and rapid production is required. Therefore, it is thought that determining the strength values with high accuracy using the developed combined methods without damaging the building element will provide benefits in terms of time, labor, and cost.
Keywords: highstrength concrete; compressive strength; non-destructive test methods; combined methods; response surface method